Kaplan & Sadock's synopsis of psychiatry - Boland, Robert Joseph; Verduin, Marcia L.; Ruiz, Pedro, 1936- (Wolters Kluwer, 2022)
The New and thoroughly updated 11th edition of Kaplan and Sadock's Synopsis of Psychiatry: Behavioral Sciences/Clinical Psychiatry is a complete overview of the entire field of psychiatry for clinicians, residents, students, and all others who provide mental health care. In this best-selling textbook in psychiatry for over 40 years, the reader will find a thorough discussion of both the behavioral sciences and clinical psychiatry. The 11th edition integrates all the DSM-5 criteria and provides a detailed and comprehensive overview of treatment methods for every known mental disorder.